Two internal critiques for theists who oppose moral enhancement on a process virtue basis - Brummett, Abram (Bioethics, 2022)
Some bioconservatives reject the use of biotechnology for moral enhancement while simultaneously purporting to accept standard theism and process virtue. Standard theism holds that God is a personal, omniscient, omnibenevolent, omnipotent, transcendent being. Process virtue holds that virtue can only be obtained through a specific process and not by means of biotechnological shortcuts. For example, proponents of the view may claim that the virtue of compassion cannot be achieved by taking a pill but must come about from organic life experience that involves suffering, and reflection. We describe two internal critiques that arise by combining standard theism and process virtue. The first critique arises when the process virtue view is applied to the concept of God himself. Because God is thought to have always been perfectly virtuous, it follows he did not obtain his virtue through a process. Theistic bioconservatives must either give up the notion that God has always been perfectly virtuous or give up their claim that virtue must be obtained through a particular kind of process. The second critique argues that rejecting moral enhancement on the basis of process virtue is selfish, which is a vice by the lights of all mainstream manifestations of standard theism. Process virtue is selfish because it requires prioritizing the development of one's own personal virtue over moral enhancement that will improve one's other-regarding virtues. We conclude that the combination of standard theism and process virtue does not serve as a strong basis from which to oppose moral enhancement.